2008
DOI: 10.1007/s10452-008-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the red shrimp Aristeus antennatus in the Eastern Mediterranean

Abstract: The relative growth of body parts (abdomen, uropod, scaphocerite, telson, rostrum and the third pereiopod) of both sexes of red shrimp Aristeus antennatus was studied in the Greek and Italian Ionian Sea (Eastern Mediterranean), at a depth range from 546 to 1,047 m. Morphometric relationships in the sexes showed similar patterns of relative growth in the two study areas. Although, morphological characters (abdomen, carapace length, pereiopod, rostrum, scaphocerite, telson, uropod and weight) of female were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…The morphometric measures reflected different aspects of its functional morphology (Sardà et al ., 2005; Kapiris & Kavvadas, 2009), such as vision (eye), defence and streamlining (rostrum), walking (pereiopod) and swimming ability (pleopod, tail, telson, uropod), orientation and maintaining direction (scaphocerite), metabolic (carapace) and reproductive (abdomen) capacity. All the morphometric variables (landmarks and distances), which were used in the present study, are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphometric measures reflected different aspects of its functional morphology (Sardà et al ., 2005; Kapiris & Kavvadas, 2009), such as vision (eye), defence and streamlining (rostrum), walking (pereiopod) and swimming ability (pleopod, tail, telson, uropod), orientation and maintaining direction (scaphocerite), metabolic (carapace) and reproductive (abdomen) capacity. All the morphometric variables (landmarks and distances), which were used in the present study, are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Rostral polymorphisms in shrimps are rather common phenomena, which can be observed in both marine (De Grave, 1999; Kapiris, 2005; Kapiris & Kavvadas, 2009) and freshwater species (Anastasiadou et al ., 2004; Ocasio-Torres et al ., 2015a). They are usually related to sexual dimorphism (d'Udekem d'Acoz, 1996; Kapiris & Thessalou-Legaki, 2001), reproductive age (Lozano-Álvarez et al ., 2007), strategies for the avoidance of predation (Jugovic et al ., 2010; Ocasio-Torres et al ., 2014, 2015b) and other micro-evolutionary factors.…”
Section: Introductionmentioning
confidence: 99%
“… ýòîì ñëó÷àå âûáîðêè ñ íèçêèìè çíà÷åíèÿìè ïðèçíàêà ïðèìåðíî íà Èçâåñòíî, ÷òî âûñîêàÿ òåìïåðàòóðà óñêîðÿåò ðàçâèòèå è ïðèâîäèò ê ôîðìèðîâàíèþ ìåëêèõ îñîáåé, íèçêàÿ òåìïåðàòóðà õàðàêòåðèçóåòñÿ ïðîòèâîïîëîaeíûì ýôôåêòîì. Òàêàÿ çàêîíîìåðíîñòü õàðàêòåðíà äëÿ áîëüøèíñòâà áåñïîçâîíî÷íûõ, â òîì ÷èñëå äëÿ êîïåïîä [Ãðå÷àíûé è äð., 1997, 2004Belmonte, 2006;Kapiris, Kavvadas, 2009].  òî aeå âðåìÿ ðàçìåðû âçðîñëûõ ñàìîê E. baicalensis îáðàòíî ñâÿçàíû ñ òåìïåðàòóðîé âîäû, â êîòîðîé îíè aeèâóò [Àôàíàñüåâà, 1995].…”
Section: ðåçóëüòàòû è èõ îáñóAeäåíèåunclassified
“…Ïîñêîëüêó àíòåííû ÿâëÿþòñÿ âàaeíûì îðãàíîì äâèaeåíèÿ ó ïëàíêòîííûõ ðàêîîáðàçíûõ, òî ìîaeíî ïðåäïîëàãàòü, ÷òî óäëèíåíèå ýòèõ îðãàíîâ èëè óâåëè÷åíèå èõ ïëîùàäè çà ñ÷åò áîëüøåãî ÷èñëà ùåòèíîê äàåò îïðåäåëåííûå ïðåèìóùåñòâà âî âðåìÿ ñîâåðøåíèÿ ñóòî÷íûõ âåðòèêàëüíûõ ìèãðàöèé ðà÷êà â óñëîâèÿõ èçìåíåíèÿ ãèäðîëîãè-÷åñêèõ ïàðàìåòðîâ. Ñâÿçü ìåaeäó ðàçìåðàìè ìîðôîëîãè÷åñêèõ ñòðóêòóð, îòâå÷àþùèõ çà ëîêîìîöèþ, è ñåçîííûì èçìåíåíèåì àêòèâíîñòè ñóòî÷íûõ ìèãðàöèé îáíàðóaeåíà è ó ñðåäèçåìíîìîðñêîé êðåâåòêè Aristeus antennàtus [Kapiris, Kavvadas, 2009].…”
Section: ðåçóëüòàòû è èõ îáñóAeäåíèåunclassified
“…Συχνά το είδος αυτό συγχέεται με ένα άλλο είδος παρόμοιου μεγέθους, την Aristeus antennatus (μωβ-κόκκινη γαρίδα βαθέων υδάτων). Οι A. antennatus ανήκουν και αυτές στην οικογένεια Aristeidae [15][16][17]. Έχουν ένα ελαφρώς κόκκινο, μαργαριταρώδες ροζ χρώμα, με βιολετί αποχρώσεις στην επιφάνεια του κεφαλοθώρακα και στις αρθρώσεις των κοιλιακών τμημάτων.…”
Section: περιγραφήunclassified